A política cultural e o espetáculo urbano : uma reflexão sobre o direito à cidade no Rio de Janeiro - Oliveira, Anita Loureiro de (2004)
This study aimed to identify, and analyze Rio de Janeiro´s cultural policy. This cultural policy guide by a logic that treats the culture likes a consumer good, encourages practices of cultural consumer and results an inequality arrange of cultural contact opportunity, apparent through an analyses on landscape of Rio de Janeiro city. This work speaks about the production of space, about the construction of the city marketing, but treats too of the resistance cultural actions as a new form of social representing.